Fingering in Vaginal Introitus: A Case of Sexual Assault In the Perspective of POCSO Act, 2012 - Phad, Laxman G; Meshram, Satin K; Ambade, Vipul N; G, Shailendra; Dixit , Pradeep G (Journal of Indian Academy of Forensic Medicine, 2015)
Childhood sexual assault is a very important topic to be discussed seriously, as the statistics regarding the cases are increasing day by day. The research literature and advocacy should focus upon improving the community responses to sexual assault cases and preventing it. The offenders must be prosecuted and treated vigorously. The newly introduced POCSO Act, 2012 (Prevention of Children against Sexual Offence Act) has made a provision for stringent and rapid dispensation of justice in such cases. In the present case, the alleged accused had inserted his right middle finger in the vaginal introitus of the victim aged Five years. Two cresentric abrasions were present on the medial aspect of thigh and one contusion on left vulva with intact hymen of the victim. There was no evidence of any injury or stains on the body of accused. The present case of ‘fingering’ in vaginal introitus is discussed in the perspective of new POCSO Act.